Love yourself well : an empowering wellness guide to supporting your gut, brain & vagina - Bosworth, Lo, 1986- (Dey St., an imprint of William Morrow, 2022)
"A frank and accessible guide to optimizing women's health by Lo Bosworth--the CEO and founder of Love Wellness--tracing the interconnectivity of the gut, brain, and vagina, and providing natural solutions to intimate problems"--